Electroanalytical applications of reduced-graphene oxide for sensing of bioanalytes / Norazriena Yusoff - Norazriena, Yusoff (2017)
The development of a sensor for the precise and selective measurement of biological analytes (such as dopamine (DA), nitric oxide (NO), hydrogen peroxide (H2O2) and L-Cysteine (L-Cys)) at the low levels characteristic of living systems can make a great contribution to disease diagnosis. The discovery of an electrochemical technique for the detection of various biological analytes was induced by the strong demand on developing a sensing technique that able to offer a rapid response, high sensitivity, simplicity and low operating cost. In order to enhance the analytical performance of electrochemical biosensor, several challenges associated with the sensors need to be solved including: (i) sluggish electron-transfer rate properties at the electrode's surface which led to the poor response signal; (ii) limited sensitivity and selectivity capabilities towards target analyte detection due to occurrence of fouling effect; and (iii) overlapping voltammetric response caused by the co-existence of various interfering species. We have sought to address these problems through chemical modification of conventional working electrode surface with an electrochemically active material, which is reduced graphene oxide (rGO)-based material. The thesis reports the preparation of novel reduced graphene oxide-nafion@metal (rGO-Nf@metal) nanohybrid materials which were then used to modify glassy carbon electrode (GCE) for the detection of various biological analytes. The strategy of using these nanohybrid materials is driven by the excellent individual properties owned by rGO and metal nanoparticles which essential in boosting the sensing performance. There are four important studies that have been presented in this thesis; (i) reduced graphene oxide-nafion (rGO-Nf) nanohybrid modified electrode for electrochemical detection of DA and NO; (ii) reduced graphene oxide-nafion@silver (rGO-Nf@Ag) nanohybrid modified electrode for electrochemical detection of H2O2; (iii) reduced graphene oxide-nafion@gold (rGO-Nf@Au) nanohybrid modified electrode for electrochemical detection of NO; (iv) reduced graphene oxide-nafion@palladium (rGO-Nf@Pd) nanohybrid modified electrode for electrochemical detection of L-Cys. To sum up, we have successfully developed a simple, highly sensitive, and selective electrochemical sensor using rGO-Nf@metal-based nanohybrids for the detection of various biological analytes. The novelty of presented work lies in the used of simple, rapid, and facile method for synthesis that is hydrothermal method, and the used of small amount of metal which could reduce the cost of production. Moreover, the combination of three individual materials (rGO, Nf, and metal nanoparticles) to form a ternary nanohybrid material proven to be suitable material for boosting the electrochemical sensor performance, thus open up a new path to develop new catalyst for electrochemical sensor.